Interpretasi Tradisi Mappacci Masyarakat Desa Pengkendekan Perspektif Hukum Islam (Ahkam: Jurnal Hukum Islam, 2022)
Abstract This study discusses the interpretation of the mappacci tradition of Pengkedekan Village from the perspective of Islamic law.  This research is qualitative.  Data was collected through direct observation and interviews.  Data analysis used an inductive method to get the conclusion.  From this research, it was found that the mappacci procession is not only applying pacci to the palms of the bride and groom.  Several series of activities that must be fulfilled are barazanji, mappanretemme and giving pacci.  Barazanji and mappanretemme are a series, the villagers of Pengekendekan do in the afternoon while giving pacci is done at night.  There are seven mappacci tools, and each utensil is a symbol, the meaning of which is hidden, so it requires deep interpretation so that the meaning of each symbol appears, and is properly understood by the bride and groom, such as 1) Pillows symbolize respect, 2) Sarong symbolizes cover, 3) Banana leaves symbolize life, 4) jackfruit leaves symbolize dreams, hopes and ideals, 5) Banno symbolizes independence, 6) candles symbolize light or illumination, 7) henna leaves symbolize the purity of the soul.  The interpretation of this tradition gives birth to the idea of structured knowledge, containing the goodness that is taught in religion.  The essence of mappacci forms norms in social life, and forms a family.
Keywords: Interpretation; Mappacci; Barazanji; Mappanretemme; Islamic Law